Floating Gate PMOS Dosimeters Under Bias Controlled Cycled Measurement - García Inza, Mariano Andrés (2011)
Floating Gate Metal Oxide Semiconductor (FG-MOS) structures, designed and fabricated in a CMOS process, were irradiated under the Bias Controlled Cycled Measurement (BCCM) novel technique conditions. Results presented in this work show the possibility of using such structures with the BCCM technique to measure ionizing radiation absorbed dose over a range of several kGy without significant loss of sensitivity. Transients observed after the bias switch are related to the evolution of the charge distribution between the floating gate and oxide traps near the semiconductor.